Gambaran Kelengkapan Resume Rekam Medis Pasien Rawat Jalan - Ni Nyoman Novia Marheni; Ni Luh Putu Devhy; Made Wahyu Aditya (STIKes Surya Global Yogyakarta, 2022)
Background of Study: One of the parameters to determine the quality of health services in hospitals is data or information from good and complete medical records. Indicators of good and complete medical record quality are content completeness, accuracy, timeliness, and compliance with legal requirements. This study aims to determine the completeness of outpatient medical records at the Wangaya Regional General Hospital.Methods: The number of samples in this study were 30 inpatient medical records obtained using the slovin formula. The sampling technique used in this study was probability sampling method with a simple random sampling technique. This research was conducted for 2 months from January-February 2021, and data analysis using SPSS.Results: From the results of the research conducted when viewed from several aspects, it was found that Based on the Identification Review, there were 33.3% incomplete, namely in filling in the telephone number. Based on the reporting review, there were 56.7% incomplete, namely in filling out treatment/ therapy and 40% incomplete in filling out physical examination. true or understandable. Based on 100% complete Authentication Review, there was the doctor's name and signature. Based on the results obtained, it can be concluded that the writing of medical records was not 100% complete.Conclusion: It is hoped that the Wangaya Regional General Hospital can improve the completeness of filling out outpatient examination forms by holding training, workshops related to the importance of filling out complete medical records.Keywords: Medical Record, Outpatient, Description Completeness